A Book Review of Charming Elements in Animation Cinema - Hamid Sadeghian; , Gity Nooreddinnejad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Media and artistic animation is a combination of other elements of the arts. This feature, in addition to the possibility of creating a fantasy universe, has a special charm that can address all age groups. In this regard, the necessity of publishing scientific and educational texts and adapting them to the latest findings, in view of the ever-increasing development of production methods, doubles the importance of this investigation. In this regard, the issue of the elements of attractiveness in the animation cinema is necessary, useful, and valuable. Despite its drawbacks, this work is one of the sources of Farsi help for students and animation enthusiasts. However, by studying the configuration of the topics and the content of the book, it can be noted that the correction is effective in advancing the goals and strengthening the content. These include lack of light unity in the structure of the content, lack of clarity in the presentation of the content for a particular or general audience, lack of attention to the impact of contemporary achievements, the need for appropriate images for the completion and explanation of the topics and the lack of proper communication between some The images presented with the text have been criticized in various ways. This paper, after introducing some points, reviews the content of the book and analyzes the contents of the book.